Design and fabrication of an electric belt sander / Puteri Nor Azwina Arifin - Arifin, Puteri Nor Azwina (2024)
An electric belt sander is a mini power tool using motorized belt that sharpens and smooths the surface of the workpiece which allows people to finish their work faster without being physically tired. Moreover, it is obvious that the problem if we are using sandpaper, it requires a lot of time and energy to finish a sanding task for a product. The main objective is to build and test an electric belt sander that will assist users, particularly in workshop for final-year Mechanical Engineering students who enrolled in FYP to do finishing to their projects' surfaces. The direct current motor that is powered in this machine can speed up the sanding process is controlled by a speed controller which people can adjust the sanding belt speed depending on their workpiece type. The significance of this project is to design and build an electric belt sander with a lower cost that can save people’s time and energy. Furthermore, it has a low maintenance cost because the only part that needs to be maintained regularly is the sanding belt once it is worn out. In a nutshell, this machine will give a lot of benefit for people who are interested in buying an affordable belt sander.